The contribution of two common shrub species to aboveground and belowground carbon stock in Iberian dehesas (Journal of Arid Environments, 2013)
Shrubs play an important role in water-limited agro-silvo-pastoral systems by providing shelter and forage for livestock, for erosion control, to maintain biodiversity, diversifying the landscape, and above all, facilitating the regeneration of trees. Furthermore, the carbon sink capacity of shrubs could also help to mitigate the effects of climate change since they constitute a high proportion of total plant biomass. The contribution of two common extensive native shrub species (Cistus ladanifer L. and Retama sphaerocarpa (L.) Boiss.) to the carbon pool of Iberian dehesas (Mediterranean agro-silvo-pastoral systems) is analyzed through biomass models developed at both individual (biovolume depending) and community level (height and cover depending). The total amount of carbon stored in these shrubs, including above- and belowground biomass, ranges from 1.8 to 11.2 Mg C ha 1 (mean 6.8 Mg C ha 1 ) for communities of C. ladanifer and from 2.6 to 8.6 Mg C ha 1 (mean 4.5 Mg C ha 1 ) for R. sphaerocarpa. These quantities account for over 20e30% of the total plant biomass in the system. The potential for carbon sequestration of these shrubs in the studied system ranges 0.10e1.32 Mg C ha 1 year 1 and 0.25e1.25 Mg C ha 1 year 1 for the C. ladanifer and R. sphaerocarpa communities’ respectively

Silviculture and Carbon Sequestration in Mediterranean Oak Forests (Managing Forest Ecosystems: The Challenge of Climate Change,, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.